Bladder Tumor Cases with History of Bladder Stones: Disparity in Histopathological Findings at RSUP Dr. Sardjito Yogyakarta - Nikko Caesario Mauldy Susilo; Indrawarman Soero Hardjo (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Bladder cancer remains a major cause of morbidity and hospitalization worldwide. Bladder stones have long been linked to squamous cell carcinoma (SCC) as a result of persistent irritation and inflammation. Nevertheless, modern histopathological patterns may diverge from this traditional framework. This study aims to delineate the histopathological distribution of bladder tumors in patients with a history of bladder stones and to investigate the divergence between predicted and actual tumor subtypes. A retrospective descriptive study was performed at RSUP Dr. Sardjito Yogyakarta from January 2018 to June 2025. We looked at medical records of patients who had bladder tumors that were confirmed by histopathology and bladder stones that were documented. A descriptive univariate analysis was conducted. There were 29 patients in all, and their average age was 59.7 ± 11.8 years. Of these, 26 (89.6%) were men. Eighteen patients (62.1%) had urothelial carcinoma/transitional cell carcinoma (UC/TCC), ten patients (34.5%) had SCC, and one patient (3.4%) had adenocarcinoma. The majority of UC cases exhibited high-grade squamous differentiation (12/18; 66.7%). Even though there were a lot of big stones and people were exposed to them for a long time, UC was still more common than SCC. These results show that bladder tumors linked to stones have different types of histopathology and that SCC may not always be the most common type in cases of chronic irritation. Additional multicenter and molecular investigations are necessary to elucidate the biological mechanisms driving this distribution.Keywords: Bladder Tumor, Bladder Stones, Squamous Cell Carcinoma, Urothelial Carcinoma, Histopathology.